Influence Of Talent Farming And Strategic Agility On Performance Of Smes In Manufacturing Industries - Palanisamy, Shanmuganathan (2022)
Manufacturing SMEs is the backbone of industrial development and an important contribution to the Malaysian economy. However, manufacturing SMEs lack of ability on adjusting to changes and preparation in talent readiness to mitigate the risk of capitalising on the opportunities in today's dynamic business landscape. Therefore, this study attempts to examine and provide empirical evidence on the relationship between the Talent and Strategic Agility influence on the performance of Malaysian manufacturing SMEs. The dimensions considered for Talent Farming in the study are talent harnessing, talent acquisition, talent retention and talent displacement. A total of 149 valid responses from a cross-sectional survey from Malaysian manufacturing SMEs were investigated using SPSS software version 24, Partial Least Squares-Structural Equation Modelling (PLS-SEM) and IPMA analysis. The findings reveal that talent retention, talent displacement and strategic agility have a significant direct influence on SMEs’ performance while Strategic Agility has mediating effects on the relationship involving talent retention and talent displacement with SME’s performance respectively. However, IPMA analysis finding highlight all talent farming dimensions are equally important to support building well-organized and robust SMEs’ performance. This study contributes a guide to SMEs for developing a sustainable and competitive business by adopting a strategic agility alignment to talent to increase their agility